Children's Criminal System as Criminal Offenders Perspective of Law Number 11 Of 2012 Concerning Children's Criminal Justice System - FAHLAVI, Ananda Alif Rizal; ASMARANI, Emma Dwi; SHELVIANA, Shelviana; DEBIANTHO, Debiantho; HAMDANI, Helmi; ASIHAY, Yayang; JOVI; DODY; KRISTHY, Mutia Evi (Indonesia Strategic Sustainability, 2023)
Purpose: This study describes the principles system of legal protection against Children as criminal perpetrators in Law of the Republic of Indonesia Law Number 11 of 2012 concerning the Juvenile Criminal Justice System refers to the Convention on The Rights of The Child, and it has covered most of the principles of child protection perpetrator as well.Methodology:The research method used in this study is normative legal research because it includes the scope of legal dogmatic learning or researching legal rules.Findings: The study also found that the provision of punishment against the child has been following that stipulated in Law Number 23 of 2002 concerning Children Protection, which states that imprisonment can be applied to the child when there is no last effort any longer and shall be executed separately from the adult prison.Implication:The child protection efforts shall be implemented by imposing restorative sentencing (restorative justice) and diversion if completing the requirement of Law Number 11 of 2012 concerning the juvenile criminal justice system.